2021
DOI: 10.1186/s40634-020-00321-y
|View full text |Cite
|
Sign up to set email alerts
|

Why are tapes better than wires in knotless rotator cuff repairs? An evaluation of force, pressure and contact area in a tendon bone unit mechanical model

Abstract: Purpose Knotless repairs have demonstrated encouraging performance regarding retear rate reduction, but literature aiming at identifying the specific variables responsible for these results is scarce and conflictive. The purpose of this paper was to evaluate the effect of the material (tape or wire suture) and medial tendon passage (single or double passage) on the contact force, pressure and area at the tendon bone interface in order to identify the key factors responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…have advantageous implications on the biological process of healing [45]. These results are aligned with our previous report [29], which demonstrated that in knotless TOE repairs with medial row sliding anchors, passing sutures individually (DP) significantly increases the contact area when compared to combined passage of suture limbs in a single pilot hole (SP).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…have advantageous implications on the biological process of healing [45]. These results are aligned with our previous report [29], which demonstrated that in knotless TOE repairs with medial row sliding anchors, passing sutures individually (DP) significantly increases the contact area when compared to combined passage of suture limbs in a single pilot hole (SP).…”
Section: Discussionsupporting
confidence: 86%
“…Also as previously reported [29], results also demonstrated that at higher lateral tension values, single‐hole passage in the medial cuff significantly increases peak force, which may provide higher focal stability but also hamper biological healing in that specific location [22], usually quite close or at the MBR [29]. Of specific interest, looking at McCarron et al [31] description of failure in continuity in which regardless of tendon healing, some tissue retraction always occurs, excessive contact force at the MBR or near it prevents this phenomenon and can, hypothetically, increase the risk of type 2 retears.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations